The Affecting Factors in the Weakness of Reading and Writing among Primary grades' pupils in Baqa'a Governorate from Teachers' Point of View - Alzubaid, Hisham Fahad Nufal (Journal of Educational and Psychological Sciences, 2021)
This study aimed to reveal the affecting factors in the Weakness of reading and writing among Primary grades' pupils from teachers' point of view. It also aimed to investigate the effect of both variables (experience in teaching, educational qualification). The sample of this study consisted of (90) teachers, who were chosen by simple random method, To achieve the aims of this study, a questionnaire was built which is consisted of (35) items. its validity was verified by presenting it to a group of specialized arbitrators, and its internal consistency was also verified in order to identify the extent of internal homogeneity of the study tool (the questionnaire) by calculating Pearson's correlation coefficients between the degree of each phrase and the total degree of the axis to which it belongs. It was found that: All the axes of the questionnaire were statistically significant at the level of (0.01). This confirms that the questionnaire has a high degree of internal consistency; therefore, it is reliable. and also, its stability was achieved by applying it to an exploratory sample consisting of (15) teachers, whereas the Total of stability coefficient ( Alpha Cronbach) was (0.874). This study adopted the descriptive approach, as it was applied in the second semester of the year 1441 AH, The results of the study found that: the affecting factors in the Weakness of reading and writing among Primary grades' pupils from the teachers' point of view came with a medium degree, with a general arithmetic average of (3.34 out of 5.00). The second axis, "pupil related factors", came in the first rank with an arithmetic average of (3.49) and with a high degree. The fourth axis, "factors related to teaching method", came in second rank with an arithmetic average of (3.42) and with a high degree. The first axis, "factors related to teacher" came in the third rank with an arithmetic average (3.40) and with a high degree. Finally, the third axis, "factors related to the course" came in the fourth rank with an average arithmetic (3.08) and with a medium degree. Based on these results, the study recommended several recommendations, including: More attention should be paid to teachers of primary grades: physical and moral incentives must be provided to them, and their daily quotas should be reduced.
Keywords: the weakness of reading and writing; primary grades